Undercover investigation - Barefoot, J. Kirk, author (Boston : Butterworth-Heinemann, 1995)
"Undercover Investigation, 3rd Edition is a comprehensive and practical guide that serves two purposes. As a reference book for security managers, it provides a blueprint for managing and developing the in-house undercover investigative function. As a text for training police officers, intelligence agents, and private security personnel, it is the bible of this specialty field, and is the only how-to book on the market."--BOOK JACKET.
Brief History of Undercover Work -- Recruiting and Selecting Undercover Personnel -- Training -- The Cover -- The Assignment -- Roping -- Entrapment and Testimony -- Supervision and Communications -- The Burn -- Shopping Investigations and Surveillance.
Includes bibliographical references and index.
Keywords: Undercover operations